Museum Goedang Ransoem Sawahlunto: dari Museum menuju Wisata Heritage tahun 2005–2019 - Fahira, Intan; Fatimah, Siti (YASIN, 2025)
Although the history of the Ombilin mining site and its infrastructural transformation has received scholarly attention, studies specifically tracing the functional transformation of the Goedang Ransoem Museum in Sawahlunto remain limited. This research aims to describe the process of functional transition of the Goedang Ransoem Museum from its inauguration as a museum to its transformation into a heritage tourism destination in the city of Sawahlunto. The study employs historical research methods, including the heuristic stage for data collection, followed by source criticism through external and internal evaluations, data interpretation, and historiographical writing as the final stage. The findings reveal that following the closure of the Ombilin mine in the early 1990s, various remnants of colonial infrastructure—including the former communal kitchen building for mine workers—underwent functional changes. The Goedang Ransoem Museum, which had previously served several non-museum functions, was officially inaugurated as a museum in 2005 and reclassified as a heritage tourism site in 2019. These findings contribute to a deeper understanding of post-industrial spatial transformation in the context of colonial heritage preservation. The implications highlight the importance of adaptive management of historical assets as part of a sustainable cultural tourism development strategy in post-mining regions.